THE EFFECTS OF READING INTEREST AND VOCABULARY MASTERY TOWARDS NARRATIVE ENGLISH TEXT WRITING SKILL - Rosanti Rosanti (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of this research  are (1) to find out the effects of reading interest and vocabulary mastery towards  narrative English  text writing skill of SMP Negeri studets in Karawang district.  (2) to find out the effects of vocabulary mastery towards narrative English text writing skill of SMP Negeri in Karawang district. This research is survey in Karawang district, academic year 2017/2018.  The number of sample is 80 students who are taken randomly by many SMP Negeri schools  in Karawang district.  Taking data of this research is questioner. Data analysis by using descriptive statistic method, validity test, reliability test, multiple regression analysis. The results of this research are (1) there is significant effect of reading interest and vocabulary mastery together towards narrative English text writing skill of SMP Negeri Students in Karawang district. It is proven by getting score  sig.0,000 < 0,05 and fcount =67,749. (2) there is significant effect reading habit  towards  narrative English text writing skill of SMP Negeri Students in Karawang district. It is proven by getting score  sig.0,000 < 0,05 and fcount =7,222. (3). There is significant effect of vocabulary mastery towards  narrative English text writing skill of SMP Negeri Students in Karawang district. It is proven by getting score sig.0,00 < 0,05 and tcount = 2,916Key words : Reading interest, vocabulary mastery,  narrative English text writing skill